Quantitative and Qualitative detect for cheat beef with chicken meat by immunological methods (Baghdad Science Journal, 2011)
beef and chicken meat were used to get Sarcoplasim, the chicken Sarcoplasim were used to prepare antibody for it after injected in rabbit, the antiserums activity were 1/32 by determined with Immune double diffusion test, the self test refer to abele for some antiserums to detected with beef sarcoplasim, which it mean found same proteins be between beef and chicken meat, which it refer to difficult depended on this immune method to detect for cheat of chicken meat with beef, so the antibody for beef sarcoplasim were removed from serum by immune absorption step to produce specific serum against chicken sarcoplasim that it used in Immune double diffusion test to qualitative detect for cheat beef with 5% chicken meat or more at least, and the Immune diffusion test were used to quantitative determined for cheat in 5-50%, this test were showed linear correlation between cheat percent and zone that it showed in gel, the evaluation test results were showed able to cheat beef by add chicken meat up to 25% with out to feel it, while the Immune diffusion test could to detect cheat in this percent and less.